ANALYSIS OF WORKING CAPITAL TURNOVER IMPACT TOWARD PROFITABILITY AND ACCOUNTING IMPLICATION AT PT. MULTI STRADA ARAH SARANA Tbk. - Muhammad Nur Rizqi (The Accounting Journal of Binaniaga, 2017)
Abstract. This research is meant to examine the working capital cash flow which are consist of three sub variables: cash flow (X1), receivable turnover (X2), and inventory turnover (X3) as the independent variables to profitability as (Y) variable. The data is taken from financial statements in form of balance sheet and income statements that have been audited at one of the national tires company, PT. Multi Strada Arah Sarana. Tbk in the past 7 years for 2010-2016 periods. Multiple linear regressions, coefficient determination, coefficient correlation and T-test are used to analyze the impact of working capital turnover, receivable turnover, and inventory turnover toward profitability in the company. In the other hand, descriptive analysis is used to analyze the accounting implication. The result of this research shows that there is 38.6%, a small impact between cash flow, account receivable turnover and inventory turnover on the coefficient determination test, but the others are 61,4%. The T-test shows that cash flow, account receivable turnover and inventory turnover has no significant impact toward ROI. This result is strengthen by F-test (Anova) which says that there is no impact between the independent variables (cash flow, receivable turnover, and inventory turnover) at the same time toward profitability (ROI). Accounting implication meant in this study is the basic impact from account receivable and inventory as current assets that shows the company sells more on credit sales. In the other hand, the inventory turnover shows that the sales really often happen. In this case, the company should pay attention to the cash flow because it will give some information about the use and the function of net cash.Keywords: capital working, ROI, and operating activity.